Revisiting the morphology, microstructure, and properties of cellulose fibre from pineapple leaf so as to expand its utilization - Budsaraporn Surajarusarn,; Paweena Traiperm,; Taweechai Amornsakchai, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Pineapple leaf waste is an agricultural product that is available in large quantities and is still under-utilized. Therefore, the aim of this work was to investigate the morphology, microstructure, and mechanical properties of pineapple leaf fibre (PALF) such that its full potential may be realized. Pineapple leaf, its fibre bundles and elementary fibres have been investigated. Morphology, size, and mechanical properties of fibre bundles extracted from different parts (i.e. bottom, middle and top) of a leaf were studied. It was found that the PALF obtained from vascular tissue and from the mesophyll have different macroscopic shapes. Both, however, contain micron-size elementary fibres of similar size and shape. Size and properties of fibre bundles change from the bottom end of a leaf toward the top end. Pineapple leaf microfibre (PALMF) was found to be smaller in diameter than other natural fibres. It is also very long and its structure changes according to its position along the leaf. At the bottom end a clear and large central hole or lumen can be observed. At the top the lumen becomes almost undetectable. The mechanical strength of PALMF appears to decrease, albeit very slightly, toward the tip of the leaf. The mechanical properties of the fibres are relatively high and comparable to that of flax and hemp fibres which are widely studied and used as reinforcing materials in composites. Very long microfibre can easily be obtained from fibre bundles by dissolving the binding matrix. Potential applications for this microfibre are suggested.